Penerapan Nilai Kejujuran dalam Pendidikan Anti-Korupsi untuk Mencegah Plagiarisme di Kalangan Mahasiswa Universitas PGRI Delta, Sidoarjo - Sari, Hesti Kartika; Safira, Marshanda Dwi Ayu; Naha, Indriyati Konga (Yayasan Amanah Nur Aman, 2025)
Plagiarism in higher education institutions represents a serious challenge that can undermine academic integrity and diminish the quality of graduates. This study aims to examine the implementation of honesty values within anti-corruption education as a preventive measure against plagiarism among students at Universitas PGRI Delta Sidoarjo. The research employs a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings reveal that the internalization of honesty values in academic activities, through an anti-corruption education curriculum, significantly contributes to the development of students’ moral awareness. Learning processes that emphasize integrity, responsibility, and critical attitudes toward manipulative actions foster autonomous anti-plagiarism behavior. Therefore, anti-corruption education integrated with the value of honesty not only shapes ethically grounded students but also serves as a vital instrument in creating an academic culture that is clean and accountable.